Sintering effects on mechanical properties of bioglass reinforced hydroxyapatite composites - (:unkn) unknown (Trans Tech Publications Ltd, 2003)
The improvement of mechanical properties of HA with reinforcement of 5 and 10 wt % bioglass (45S5) with different sintering temperatures was studied. Although HA shows good biocompatibility with human body, its applications are limited to nonload-bearing areas due to its low mechanical properties. In this study naturally produced HA from human teeth is sintered with varying addition of 5 wt % and 10 wt % bioglass at 1200 and 1300°C for 4 hours. The density, microhardness measurements and compressive tests are performed and microstructural characterizations are carried out in order to find the optimum sintering temperature. Finally average hardness value of 383±60 HV (kg/mm2), average density of 2.72±0.01g/cm3, and compressive strength value of σavr=82.96±34 MPa were achieved by sintering at 1200°C with the addition of 10 wt % bioglass in HA.
Keywords: Bioglass; Composite; Dental materials; Hydroxyapatite; Mechanical properties